2009
DOI: 10.1002/poc.1599
|View full text |Cite
|
Sign up to set email alerts
|

Towards a unified view of the solvatochromism of phenolate betaine dyes

Abstract: An attempt has been made in order to unify the three types of solvatochromisms (negative, positive and inverted) of phenolate betaine dyes by a working model which describes them as particular cases of a general behavior. The model, based on the calculation (gas phase) of the chemical hardness of donor and acceptor fragments, was applied to 56 examples from the literature. As a result, the investigated compounds were grouped according to the sum of the hardnesses of their (non-interacting) fragments, this sum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…In continuation to our on-going research interest [14] on the evaluation of anticancer properties of relatively unexplored metallomacrocyclic dithiocarbamate complexes and in the light of a wide range of pharmacological activities exhibited by sulfone derivatives, [41][42][43][44][45][46] we have derivatize dap to obtained a novel series of organic diamines L 1 -L 3 and their ensuing transition metal metallomacrocyclic dithiocarbamate complexes 1 a-1 c, 2 a-2 c, 3 a-3 c. All the new compounds were structurally characterized by FT IR, MS, 1 H, 13 C, 1 H DOSY NMR spectroscopy, UV-visible, fluorescence spectrophotometers and by thermogravimetric analysis. The geometry of the compounds has been optimized by density functional theory and electrochemical responses have also been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In continuation to our on-going research interest [14] on the evaluation of anticancer properties of relatively unexplored metallomacrocyclic dithiocarbamate complexes and in the light of a wide range of pharmacological activities exhibited by sulfone derivatives, [41][42][43][44][45][46] we have derivatize dap to obtained a novel series of organic diamines L 1 -L 3 and their ensuing transition metal metallomacrocyclic dithiocarbamate complexes 1 a-1 c, 2 a-2 c, 3 a-3 c. All the new compounds were structurally characterized by FT IR, MS, 1 H, 13 C, 1 H DOSY NMR spectroscopy, UV-visible, fluorescence spectrophotometers and by thermogravimetric analysis. The geometry of the compounds has been optimized by density functional theory and electrochemical responses have also been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The optical properties of various merocyanines16 have been extensively studied and they typically show negative solvatochromic behavior (i.e., a blue shift in their absorption spectra). However, in less‐polar‐ or non‐polar solvents, such as CHCl 3 , they display a red shift in their absorption spectra, with a solvatochromic‐reversal behavior that has been the subject of some controversy in the literature 1921. Several underlying mechanisms have been proposed to explain this behavior, such as the aggregation of dye molecules in non‐polar solvents1921 and changes in molecular geometry (neutral‐ to zwitterionic‐like through a cyanine‐like structure) owing to the increase in solvent polarity 1921.…”
Section: Resultsmentioning
confidence: 99%
“…However, in less‐polar‐ or non‐polar solvents, such as CHCl 3 , they display a red shift in their absorption spectra, with a solvatochromic‐reversal behavior that has been the subject of some controversy in the literature 1921. Several underlying mechanisms have been proposed to explain this behavior, such as the aggregation of dye molecules in non‐polar solvents1921 and changes in molecular geometry (neutral‐ to zwitterionic‐like through a cyanine‐like structure) owing to the increase in solvent polarity 1921. In fact, our previous calculations on Brooker′s merocyanine dye supported this latter mechanism, that is, a change in molecular structure from neutral to zwitterionic in polar environments is responsible for the solvatochromic reversal 22.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanistic study revealed that these hybrids could inhibit P. falciparum MO15-related protein kinase (Pfmrk), an essential role in cell cycle control and differentiation in P. falciparum, and IC 50 values were 9-38 μM. [94] Besides the chalcone hybrids mentioned above, chalcone-furan/ thiophene, [95,96] chalcone-indole, [97] chalcone-pyrimidine, [98] and chalcone-sulfamide [99][100][101] hybrids also showed certain antiplasmodial activity, but the majority of them were not superior to the references.…”
Section: Chalcone-quinoline Hybridsmentioning
confidence: 99%